2019
DOI: 10.4055/cios.2019.11.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Fixed- versus Variable-Angle Locking Screws for Distal Humerus Comminuted Fractures

Abstract: Background To compare the stability of fixed- versus variable-angle locking constructs for the comminuted distal humerus fracture (AO/OTA 13-A3). Methods Eight pairs of complete humeri harvested from eight fresh frozen cadavers were used for the study. We fixed the intact humeri using 2.7-mm/3.5-mm locking VA-LCP stainless steel distal humerus posterolateral (nine-hole) and medial (seven-hole) plates. An oscillating saw was used to cut a 1-cm gap above the olecranon fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This conflicts with another study on double plating of IAFs, which demonstrated that fixed-angle transverse screws produced lower axial stiffness and strength when using parallel plates, but the trend was reversed for perpendicular plates [ 51 ]. Double plating of EAFs using only fixed-angle transverse screws provided higher axial stiffness and force at smaller, but not at larger, construct displacements versus double plating using only variable-angle screws [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…This conflicts with another study on double plating of IAFs, which demonstrated that fixed-angle transverse screws produced lower axial stiffness and strength when using parallel plates, but the trend was reversed for perpendicular plates [ 51 ]. Double plating of EAFs using only fixed-angle transverse screws provided higher axial stiffness and force at smaller, but not at larger, construct displacements versus double plating using only variable-angle screws [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Distal humerus fractures in older adults present a challenge for orthopedic surgeons. [19][20][21] The classic treatment for undisplaced fractures is cast immobilization. 8,22,23 However, due to high nonunion rates, 23 rigid fixation and early return to function to avoid loss of elbow motion are the goals of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Similarly, no difference in stiffness of construct in stress-strain curve while using VA-LCP as compared to fixed counterparts was noted in biomechanical testing in distal humerus comminuted fracture models. [9] There was also no screw breakdown or failure at plate-screw interface thus making it an alternative implant in selected cases.…”
Section: Variable-angle Locking Platesmentioning
confidence: 90%